THE INFLUENCE OF METABOLIC SYNDROME ON THE RISK OF 1ST TYPE DIABETES COMPLICATIONS DEVELOPMENT - N. V. Leonova; G. A. Chumakova; A. V. Tsirikova; S. V. Pushkareva (Российский кардиологический журнал, 2015)
Metabolic syndrome (MS) is almost always associated with diabetes of 2nd type. However recent data puts that MS might develop in patients with 1st type diabetes (DM1), and insulin resistance as its base may lead to worsening of macro- and microvascular complications.Aim. To study prevalence of MS among patients with DM1 and its influence on micro- and macrovascular complications development in the latter. Material and methods. From DM registry of Altai Region for the year 2014 we made a selection DM1 patients, totally including 3190 persons. All patients were grouped into 2 groups: with MS and without MS. In each group we studied the prevalence of angiopathies. Prevalence of complications was estimated separately for men and women. Then we standardized the parameters of DM complications prevalence by the age and gender.Results. MS in DM1 patients in our study was found in 7,1% patients. Among those with DM1 MS was statistically more prevalent in women, than in men. Group of DM1 and MS patients was older by 13±2,4years, with longer DM duration; among them the prevalence of cardiometabolic risk factors was higher. Standardization by age and gender showed that MS in DM1 statistically more significantly increased the riskretinopathy, nephropathy, polyneuropathy, angina and myocardial infarction. Thereare gender differences in MS influence on the complications risks of DM: in womenMS increases the risk of retinopathy, nehropathyand polyneuropathy; in men —onlymacroangiopathies.Conclusion. MS increases the risk of micro- and macroangiopathies in DM1patients; there are gender differences in MS influence on DM1 development. MS inDM1 requires not only glycemia control, but other MS associated parameters too.